COMPARISON OF DENTAL CARIES STATUS OF TYPE-2 DIABETICS WITH NONDIABETICS - Imran Khan (Army Medical College Rawalpindi, 2019)
Objectives: To determine the association of type-2 Diabetes Mellitus with dental caries by using decayed, missing and filled teeth index.